2017
DOI: 10.3389/fimmu.2017.00795
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Side Effects of Using Placenta-Derived Decidual Stromal Cells for Graft-versus-Host Disease and Hemorrhagic Cystitis

Abstract: Mesenchymal stromal cells (MSCs) are increasingly used in regenerate medicine. Placenta-derived decidual stromal cells (DSCs) are a novel therapy for acute graft-versus-host-disease (GVHD) and hemorrhagic cystitis (HC) after allogeneic hematopoietic stem cell transplantation (HSCT). DSCs are more immunosuppressive than MSCs. We assessed adverse events and safety using DSCs among 44 treated patients and 40 controls. The median dose of infused cells was 1.5 (range 0.9–2.9) × 106 DSCs/kg. The patients were given … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 50 publications
4
50
0
Order By: Relevance
“…Based on the findings in this study and the safety report, it appears that treatment with DSCs is safe . The causes of SAEs and deaths were infections, relapse, and other common complications seen among patients undergoing HSCT, especially those with severe acute GVHD.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Based on the findings in this study and the safety report, it appears that treatment with DSCs is safe . The causes of SAEs and deaths were infections, relapse, and other common complications seen among patients undergoing HSCT, especially those with severe acute GVHD.…”
Section: Discussionmentioning
confidence: 54%
“…We also saw a high frequency of invasive fungal infection in the controls and in patients treated with MSCs . In a safety study, we found that the side effects and causes of death were similar in patients with GVHD and hemorrhagic cystitis who were treated with DSCs and in controls treated with other therapies . Because the patients treated with DSCs have survived longer than expected, they have had more time to experience severe adverse events after HSCT complicated by acute GVHD and heavy immunosuppressive treatment.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Heparin has been shown as an effective method of preventing the CCT procoagulant effect in in vitro human studies and in vivo animal studies . In an in vivo human study, Baygan et al demonstrated a successful anticoagulation protocol using heparin for the delivery of decidual stromal cells for hemorrhagic cystitis and graft versus host disease after allogenic hematopoietic stem cell transplantation. We demonstrate that simple dilution of CCT treatments will decrease the procoagulant effect regardless of tissue type.…”
Section: Discussionmentioning
confidence: 99%
“…The patients treated with DSCs for HC have a more favorable TRM than those treated conservatively [8]. Regarding toxicity using DSCs, we performed a detailed study including 44 patients treated for acute GVHD or HC and compared them to historical controls [44]. It was a detailed study of safety and side-effects using a novel clinical therapy: DSCs for acute GVHD in 34 patients, and HC in 10 patients.…”
Section: Discussionmentioning
confidence: 99%